2021
DOI: 10.3390/plants10071485
|View full text |Cite
|
Sign up to set email alerts
|

Anything New under the Sun? An Update on Modulation of Bioactive Compounds by Different Wavelengths in Agricultural Plants

Abstract: Plants continuously rely on light as an energy source and as the driver of many processes in their lifetimes. The ability to perceive different light radiations involves several photoreceptors, which in turn activate complex signalling cascades that ultimately lead to a rearrangement in plant metabolism as an adaptation strategy towards specific light conditions. This review, after a brief summary of the structure and mode of action of the different photoreceptors, introduces the main classes of secondary meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 228 publications
4
17
0
Order By: Relevance
“…No previous studies have reported the influence of UV-B exposure on such health-promoting compounds specifically in flaxseed sprouts or microgreens. However, many manuscripts have investigated UV-B-induced effects in several crops, mostly agreeing on the general positive impact of UV-B irradiation on the total phenolic content [16]. In accordance with our results, a pre-harvest UV-B supplementation increased the total phenolic and flavonoid concentration in basil [70,71] and lettuce [72].…”
Section: Uv-b Treatment Negatively Impacts the Productivity And The P...supporting
confidence: 90%
See 2 more Smart Citations
“…No previous studies have reported the influence of UV-B exposure on such health-promoting compounds specifically in flaxseed sprouts or microgreens. However, many manuscripts have investigated UV-B-induced effects in several crops, mostly agreeing on the general positive impact of UV-B irradiation on the total phenolic content [16]. In accordance with our results, a pre-harvest UV-B supplementation increased the total phenolic and flavonoid concentration in basil [70,71] and lettuce [72].…”
Section: Uv-b Treatment Negatively Impacts the Productivity And The P...supporting
confidence: 90%
“…Conversely, flavonoids were more concentrated in microgreens than in sprouts, which might be due to the older developmental stage and consequently the longer light exposure prior to harvesting. Indeed, it is well known that flavonoid biosynthesis and accumulation are strongly influenced by light exposure, both in terms of quality and quantity [16,44,45]. The influence of light in phenolic biosynthesis and accumulation is well visible when comparing our results with those obtained by Puccinelli et al [28].…”
Section: The Growth Stage Of Sprouts and Microgreens Influences Bioma...supporting
confidence: 80%
See 1 more Smart Citation
“…Recent studies have highlighted the possibility of regulating seedling growth and increasing the content of pivotal nutritional compounds and secondary metabolites through appropriate regulation of the light spectrum used during germination. Many recent studies underlined the diversity of response of several crops towards different light conditions, in terms of both quality (wavelength) and dose (intensity and duration of exposure) [20,21]. Particularly, recent studies on microgreens and sprouts have shown the strong influence of red-and blue-light supplementation on carotenoids, chlorophylls, and phenolics accumulation in several plants of food interest, e.g., soybean, mustard, beet, pak choi, and parsley [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, physical elicitation produced by the light perceived can be controlled to trigger the activation of the plant secondary metabolism as a defence mechanism against light incidence through the use of LEDs, also stimulated by photoreceptors and genes that are activated against abiotic stresses [7].…”
Section: Introductionmentioning
confidence: 99%